2013
DOI: 10.1021/es402646c
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Assessment of a Chlorinated Drinking Water Concentrate in a Rat Multigenerational Reproductive Toxicity Study

Abstract: Some epidemiological studies report associations between drinking water disinfection byproducts (DBPs) and adverse reproductive/developmental effects, e.g., low birth weight, spontaneous abortion, stillbirth, and birth defects. Using a multigenerational rat bioassay, we evaluated an environmentally relevant "whole" mixture of DBPs representative of chlorinated drinking water, including unidentified DBPs as well as realistic proportions of known DBPs at low-toxicity concentrations. Source water from a water uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…Concentrations of each component DBP are listed in Table 1 . Chemical proportions were based on those reported at the water utility that provided water for our whole-mixture toxicity studies ( Narotsky et al 2012 , 2013 ); these proportions were held constant across dose levels (0, 500×, 1,000×, or 2,000× of the MCLs). Overall dose levels were selected based on results of a preliminary dose-range–finding study with pregnant and lactating rats.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Concentrations of each component DBP are listed in Table 1 . Chemical proportions were based on those reported at the water utility that provided water for our whole-mixture toxicity studies ( Narotsky et al 2012 , 2013 ); these proportions were held constant across dose levels (0, 500×, 1,000×, or 2,000× of the MCLs). Overall dose levels were selected based on results of a preliminary dose-range–finding study with pregnant and lactating rats.…”
Section: Methodsmentioning
confidence: 99%
“…On PND0, pups were examined for evidence of nursing (i.e., abdominal milk bands) and were sexed, counted, and weighed. In addition, 15 F 1 litters each from the control group and the high-dose group (2,000×) were selected randomly, and the anogenital distance (AGD) of each pup was measured as described previously ( Narotsky et al 2013 ). On PND6, pups were again sexed, counted, and weighed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Endocrine disruptors are capable of altering neural transmission and the formation of neural networks (Kajta and Wójtowicz, 2013). Animal studies, using artificial mixtures of DBPs detected in drinking water, observed endocrine disrupting effects, but these effects were not found when using trihalomethanes or haloacetic acids alone (Narotsky et al, 2015(Narotsky et al, , 2013. Thus, the driving agents of the DBP mixture toxicity and implicated mechanisms remain an active area of investigation (Plewa et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A study on F344 rats examining in utero exposure reported pregnancy loss following daily gavage administration (at 1  mL/ kg bodyweight) of three different DBP mixtures (ie, THM4, HAA5 (haloacetic acid, HAA5: the sum of monochloroacetic acid (MCAA), dichloroacetic acid (DCAA), trichloroacetic acid (TCAA), monobromoacetic acid (MBAA), dibromoacetic acid (DBAA)), DBP9 (ie, the sum of THM4 and HAA5)). 14 Another study in Sprague-Dawley rats reported no associations for a DBP mixture including 75 priority and regulated DBPs 15…”
Section: Introductionmentioning
confidence: 99%